(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2024)
Background: Extended exposure to antimicrobial drugs can lead to genetic changes in pathogens, resulting in resistance to specific antibiotics and posing significant public health challenges. This study aims to address this issue by synthesizing and characterizing a novel Co(II) complex with ((2,2’-(7,7’-dimethyl-2,2’-dioxo-1,1’,2,2’-tetrahydro-3H,3’H-5,5’-biindole-3,3’-diylidene)dihydrazinecar bothioamide), denoted as ligand(L). The potential antibiotic activity of this complex is evaluated in vitro against three pathogens: E. coli ATCC 25922, P. mirabilis ATCC 14153, and S. pneumoniae ATCC 49619. Methods: The novel Co(II) complex [Co2 (L)Cl2] was synthesized by reacting one mole of L with 2 moles of CoCl2, yielding the general formula [Co2LCl2]. Characterization was performed using FT-IR, 1H-NMR, UV-visible spectra, and elemental analysis (CHNS). The antimicrobial activity was evaluated by determining the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). Additionally, the synergistic effects of L and [Co2(L)Cl2] complex with ciprofloxacin (Cip) were tested against E. coli and P. mirabilis. Results: The characterization confirmed the structure of the [Co2(L)Cl2] complex, indicating successful coordination via nitrogen, oxygen, and sulfur, exhibiting a square planar geometry. Both the L and [Co2(L)Cl2] complex exhibited antimicrobial activity against the tested pathogens. Additionally, when used in combination with ciprofloxacin, both the L and the [Co2(L)Cl2] complex showed synergistic effects against E. coli and P. mirabilis, with the [Co2(L)Cl2] complex exhibiting greater efficacy. Conclusions: The novel [Co2(L)Cl2] complex demonstrated higher antimicrobial activity than the L and showed synergistic effects with ciprofloxacin against specific pathogens. As a result of this study, these two compounds show potential as antibacterial drugs.